2013
DOI: 10.1088/0029-5515/53/7/073016
|View full text |Cite
|
Sign up to set email alerts
|

Scrape-off layer properties of ITER-like limiter start-up plasmas in JET

Abstract: Recent experiments at JET combining reciprocating probe measurements upstream and infrared thermography at the plasma-facing components (PFC) on plasmas in limiter configurations show that the common approach to predicting the power load on the limiter underestimates the heat flux at the contact point by a factor 1.5–3. The current model and scaling laws used for predicting the power load onto the first wall during limiter current ramp-up/down in ITER are uncertain and a better understanding of the heat transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 20 publications
4
61
0
Order By: Relevance
“…In all previous dedicated experiments [3,4,6,7], the near SOL of inboard-limited plasmas had always been observed at the HFS. Still, no consensus could be reached on the presence of the near SOL on the LFS, being evident in C-Mod [7], not in DIII-D [6] and COMPASS [5], while no outboard measurements were available in TCV in Ref.…”
Section: Comparison With the Lfs Measurementsmentioning
confidence: 94%
See 2 more Smart Citations
“…In all previous dedicated experiments [3,4,6,7], the near SOL of inboard-limited plasmas had always been observed at the HFS. Still, no consensus could be reached on the presence of the near SOL on the LFS, being evident in C-Mod [7], not in DIII-D [6] and COMPASS [5], while no outboard measurements were available in TCV in Ref.…”
Section: Comparison With the Lfs Measurementsmentioning
confidence: 94%
“…However, recent infrared (IR) thermography and Langmuir probes (LPs) measurements of inboardlimited L-mode plasmas in many tokamaks [3,4,5,6,7] have shown the ubiquitous presence of two regions in the SOL: a "near" SOL, extending typically a few mm from the LCFS, characterized by a steep gradient of the parallel heat flux, and a "far" SOL, typically a few cm wide, featuring flatter heat flux profiles. The parallel heat flux radial profile in the SOL is therefore better described by a sum of two exponentials q || (r u ) = q n exp(−r u /λ n ) + q f exp(−r u /λ f ) ,…”
Section: Page 1 Of 26 Author Submitted Manuscript -Nf-101877r2mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] These theoretical investigations 6 focused mainly on the toroidally limited SOL, 7-9 a configuration that is relevant to the ITER start-up and ramp-down phases during which the inner or the outer vessel wall will be used as the limiting surface. 10,11 In this scenario, using low-frequency fluid models, the turbulent regimes were identified. It was found that drift waves (DW) and ballooning modes (BM) drive the plasma turbulent dynamics, with the resistive BM being the main drive in typical existing tokamak conditions, 12 a result in agreement with previous experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Since this part of the tokamak vessel is not designed to handle large particle and heat fluxes as are the divertor plates, the start-up scenario must be carefully tailored to minimize its power load. In the last few years, dedicated experiments have been conducted in a number of tokamaks in order to characterize the fluctuations and equilibrium profiles in the scrape-off layer (SOL) of limited plasmas [2][3][4][5][6][7][8]. Substantially large asymmetries have been observed between the different explored configurations, e.g.…”
Section: Introductionmentioning
confidence: 99%